Russia’s Role in World Politics
V, 120 p.
Keywords: This book explores Russia's role in world politics. In recent years, Moscow has played an increasingly active and assertive role in geopolitics. Examples include Russia’s takeover of Crimea and meddling in eastern Ukraine; Russia’s military intervention in Syria and support for the Assad government; the Kremlin’s alleged interference in the 2016 US presidential race; the pursuit of closer economic and diplomatic ties with China; and Russia’s ambitious military reforms and nuclear brinkmanship.Not surprisingly, Russia’s role in world politics has become the object of a spirited debate among Western policymakers, think-tank analysts, and academics. Much of this debate focuses on one central question: What are the main drivers, or causes, of Moscow’s recent assertiveness? The contributions gathered here address this question by focusing on the interplay of power, ideas, and domestic influences. Previously published in International Politics Volume 56, issue 6, December 2019.